SOSIALISASI DAN DEKLARASI SEKOLAH ANTI BULLYING DI SMP NASIONAL BANAU KOTA TERNATE - Bahtiar, Bahtiar (Jurnal Terapan Abdimas, 2024)
Abstract. SMP Nasional Banau Kota Ternate is one of the private schools under Yayasan Pendidikan Nasional (YPN) Maluku Utara, located in Kalumata, South Ternate subdistrict, Ternate City. SMP Nasional Banau Kota Ternate was continues to strive to improve educational services for its students, according to the expectations of the local community. One of the factors that hinders the learning process and educational activities in schools is bullying among students. Bullying of students occurs face-to-face and through social media platforms. The objectives of this community service is to increase positive attitudes in preventing bullying behavior among students at school. The implementation of the socialization and declaration SMP Nasional Banau Kota Ternate  was carried out smoothly and in an orderly manner, all participants were very enthusiastic about participating in this program. Implementation of a series of outreach and declarations as an anti-bullying school is able to build positive attitudes of students in preventing bullying behavior in schools. The bullying prevention socialization and anti-bullying school declarations as a preventive effort against acts of violence in schools be carried out continuous, consistent, well-planned, and involve relevant stakeholders. Abstrak. SMP Nasional Banau Kota Ternate adalah salah satu sekolah swasta di bawah Yayasan Pendidikan Nasional (YPN) Maluku Utara, terletak di kelurahan Kalumata kecamatan Ternate Selatan, Kota Ternate. SMP Nasional Banau terus berupaya meningkatkan pelayanan pendidikan kepada peserta didiknya sesuai dengan tuntutan masyarakat di sekitarnya. Salah satu faktor yang masih menghambat proses belajar dan aktivitas pendidikan di sekolah adalah kasus bullying di kalangan siswa. Bullying terhadap siswa tidak hanya terjadi secara face-to-face, juga terjadi pada platform media sosial. Tujuan pengabdian kepada masyarakat ini adalah untuk meningkatkan sikap positif siswa dalam mencegah prilaku bullying pada kalangan siswa di sekolah. Pelaksanaan seluruh rangkaian sosialisasi dan deklarasi SMP Nasional Banau Kota Ternate berlangsung lancar dan tertib, seluruh peserta sangat antusias mengikuti kegiatan ini. Pelaksanaan seluruh rangkaian sosialisasi dan deklarasi sebagai sekolah anti bullying mampu membangun sikap-sikap positif siswa dalam mencegah prilaku bullying di sekolah. Sosialisasi pencegahan bullying dan deklarasi sekolah anti bullying sebagai upaya preventif terhadap tindak kekerasan di sekolah perlu dilaksanakan secara terus menerus dan konsisten, dan terncana, serta melibatkan stakeholder terkait.